Tumor-targeted costimulation with antibody-fusion proteins improves bispecific antibody-mediated immune response in presence of immunosuppressive factors - Sabrina Sapski; Nadine Beha; Roland Kontermann; Dafne Müller (OncoImmunology, 2017)
Therapeutic strategies aiming for the induction of an effective immune response at the tumor site can be severely hampered by the encounter of an immunosuppressive microenvironment. We investigated here the potential of concerted costimulation by tumor-directed antibody-fusion proteins with B7.1, 4–1BBL and OX40L to enforce bispecific antibody-induced T cell stimulation in presence of recognized immunosuppressive factors including IL-10, TGF-β, indoleamine 2,3-dioxygenase (IDO), PD-L1 and regulatory T cells. The expression and activity of these factors was demonstrated in the HT1080-FAP/PBMC co-culture setting, where individual and combined costimulation were still capable to enhance T cell stimulation, even though the general activation level was reduced. Additional blockade of TGF-ß or PD-1 resulted especially effective in further enhancing the degree of T cell activation. Here, best outcome was achieved by combined costimulation of targeted 4–1BBL and B7.1. Furthermore, their individual impact on the proliferation of naïve, memory and effector CD8+ and CD4+ T cell subsets, suggest the coverage of a comprehensive T cell response. Thus, our costimulatory antibody-fusion proteins show great potential to support T cell activation in adverse conditions dictated by the tumor microenvironment.